PENGARUH PENDAPATAN BUNGA, SECURE DAN MATURITY TERHADAP RATING SUKUK KORPORASI DENGAN PRODUKTIVITAS SEBAGAI PEMODERASI - Utami, Tri; Angraini, Dila; Annisa, Dea (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2023)
This research was conducted to determine the effect of interest income, security and maturity on corporate sukuk ratings and productivity as a moderating variable (an empirical study of sukuk issuing companies listed on the Indonesia Stock Exchange in 2016-2020). The sampling method of this study used a purposive sampling method. Samples were obtained from 8 (eight) companies so that the number of observational data was 40 financial statements. The analysis technique used is multinomial logistic regression and this type of research is quantitative. The results showed that partially interest income and maturity had an effect on the sukuk rating while secure had no effect on the sukuk rating in the moderated regression analysis (MRA) test. The productivity variable as a moderating variable was able to moderate the maturity relationship with the sukuk rating but could not moderate the relationship between interest income and secure against sukuk rating.